A systematic review and conceptual framework of supply chain agility as a strategic enabler of firm competitiveness - Conrad Ochego Mogaka; Annpiera Njururi (Journal of Sustainable Development of Transport and Logistics)
Purpose: This study aims to explore supply chain agility as a strategic facilitator of firm competitiveness by critically analyzing existing literature and proposing a research agenda based on a conceptual framework. Methodology: A systematic literature review and co-citation analysis were conducted, examining 22 research papers from 1999 to 2024 sourced from reputable academic journals. Results: The study identifies key dimensions of supply chain agility, including responsiveness, flexibility, visibility, competency, resilience, and adaptability. It categorizes existing literature into modeling enablers, adoption, implementation, and agility measurement for enhancing competitiveness. A contemporary structure and framework for supply chain agility is presented. Theoretical contribution: The paper provides a comprehensive review of fundamental concepts related to supply chain agility and competitiveness, offering a conceptual framework that enhances the understanding of agile capabilities in both public and private sectors. Practical implications: The findings offer insights for supply chain managers on maintaining competitiveness in volatile markets, providing knowledge on adopting, implementing, and measuring agility throughout the supply chain.